EVALUATION OF LUXURY AND COMFORT CONDITIONS IN 18TH CENTURY ISTANBUL HOUSE FROM MUHALLEFAT MANUSCRIPTS - Ozyalvac, Sukriye Pinar Yavuztusrk (YILDIZ TECHNICAL UNIV, 2015)
In ottoman society, opportunity of acquiring luxurious elements stands out as an upper-class practice. In this study Ottoman state archive documents was used to examine the issue in context of house, and the data obtained were assessed within the context of their physical properties and urban locations. Consequently, the diversity and the prevalence of house components was determined and their purposes are shown through period documents.
Keywords: Luxury; muhallefat; ottoman house; Engineering